2020
DOI: 10.32598/jams.23.cov.5797.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Manifestation and Mortality Rate in COVID-19 Patients With Underlying Diseases

Abstract: Background and Aim: The new Coronavirus Disease 2019 (COVID-19) outbreak initiated from China in late December 2019, has posed a great global health threat. Since patients with high blood pressure, diabetes, and cardiovascular diseases are at high risk of COVID-19, this study aims to investigate the prevalence, severity, clinical manifestations, and mortality rate in COVID-19 patients with underlying diseases compared to those without underlying diseases. Methods & Materials: This study was performed on 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“… 6 In another study in Iran, the mortality rate of COVID-19 was 27.8% among the patients who suffered from CAD. 7 …”
Section: Introductionmentioning
confidence: 99%
“… 6 In another study in Iran, the mortality rate of COVID-19 was 27.8% among the patients who suffered from CAD. 7 …”
Section: Introductionmentioning
confidence: 99%
“…All patients were divided into two groups based on their blood oxygen levels, of whom 53.7% had a level under 93%, while 46.3% had a level above 93%. 23 20 The findings of this study showed a significant relationship between the disease outcome with dizziness, impaired consciousness, and seizures. A higher percentage of patients with dizziness and headache recovered, while a higher rate of patients with consciousness disorders and seizures died.…”
Section: Resultsmentioning
confidence: 54%
“…Intubations were performed on 27% of all patients, and 21.9% died. All patients were divided into two groups based on their blood oxygen levels, of whom 53.7% had a level under 93%, while 46.3% had a level above 93% 23 . Ling et al (2020) evaluated 214 patients in China, of whom 88 (41.1%) were severe and 126 (58.9%) were nonsevere.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies in Iran, the average age of patients who died with COVID-19 significantly increased after the start of the pandemic, which is in line with our aforementioned cases. [36][37][38] It has been reported…”
Section: Discussionmentioning
confidence: 99%